Acoustic Correlates Of Harmony Classes In Somali - Kimper, Wendell; Bennett, Wm. G.; Green, Christopher; Yu, Kristine (My University, 2019)
In this paper, we present pilot data from a small number of native speakers of Somali, investigating the acoustic correlates of the tongue root and/or voice quality feature relevant to vowel harmony in that language. We find statistically detectable differences along the predicted acoustic dimensions (on the basis of previous articulatory descriptions), and use Linear Discriminant Analysis (LDA) to extend classifications to previously-uncategorized items. However, we find no clear evidence that these differences are categorical or phonological.
Keywords: Somali; Acoustic correlates; Linear Discriminant Analysis